Connectivity and growth: financial centres in investment banking networks - Pažitka, V; Urban, M; Wojcik, D (SAGE Publications, 2021)
We investigate the effect of urban network connectivity on the growth of financial centres. While existing research recognizes the importance of network connectivity to firms, clusters as well as city-regions, large sample empirical evidence is currently scarce, particularly in the context of financial services. We contribute to this debate by studying underwriting of equity and debt securities, which represent some of the core activities of financial centres. We operationalise our analysis using a proprietary dataset collated from Dealogic Equity Capital Market and Debt Capital Market databases covering over 1.7 million interactions of investment banks with issuers across 540 cities globally during the 1993–2016 period. We estimate our regression equations using the System Generalized Method of Moments estimator, which allows us to obtain consistent coefficient estimates on potentially endogenous regressors, including network connectivity variables. We identify a clear pattern of positive association between network centrality of financial centres and their growth. We distinguish between intra-city and inter-city network connectivity and find that financial centres with a larger number of intercity network ties and assortative intra-city networks grow faster, while intra-city network density does not appear to affect financial centre growth. Our results on inter-city network ties are broadly consistent with established knowledge on cluster networks. In contrast, our findings on financial centres’ intra-city networks contradict previous research, which suggests that dense and disassortative intra-cluster networks aid economic performance of clusters